Can the “Five Challenges” Overcome the Problem of “Reform Without Change” in Medical Education? Reexamining the “Hidden Curriculum” - Manabu Murakami; Akiko Takeuchi; Shigeki Jin; Kotaro Matoba (Acta Médica Portuguesa, 2023)
N/a.